Tuberculosis Infection in Children and Adolescents - Tchakounte Youngui, Boris; Tchounga, Boris Kevin; Graham, Stephen M.; Bonnet, Maryline (Pathogens (Basel), 2022)
The burden of tuberculosis (TB) in children and adolescents remains very significant. Several million children and adolescents are infected with TB each year worldwide following exposure to an infectious TB case and the risk of progression from TB infection to tuberculosis disease is higher in this group compared to adults. This review describes the risk factors for TB infection in children and adolescents. Following TB exposure, the risk of TB infection is determined by a combination of index case characteristics, contact features, and environmental determinants. We also present the recently recommended approaches to diagnose and treat TB infection as well as novel tests for infection. The tests for TB infection have limitations and diagnosis still relies on an indirect immunological assessment of cellular immune response to Mycobacterium tuberculosis antigens using immunodiagnostic testing. It is recommended that TB exposed children and adolescents and those living with HIV receive TB preventive treatment (TPT) to reduce the risk of progression to TB disease. Several TPT regimens of similar effectiveness and safety are now available and recommended by the World Health Organisation.